Analisis Kloramfenikol dalam Sampel Sediaan Tetes Telinga di Kota Palembang dengan Metode Kromatografi Cair Kinerja Tinggi - Mauizatul Hasanah; Putri Wahyuni (Jurnal Penelitian Sains, 2018)
Determination of Chloramphenicol content in ear drops has been performed with high performance liquid chromatography (HPLC) method. The purpose of this research was to determination and know the sui-tability of Chloramphenicol contents in ear drops by reversed phase reversed phase with ultraviolet detector at a wavelength of 273.4 nm. The C18 column was used as stationary phase, methanol : water (70 : 30) v/v as mobile phase, with flow rate of 1 ml/minute. Determination of calibration curve linearity showed a linear cor-relation between the peak area and chloramphenicol concentration with concentration 5-25 μg/ml (r = 0,998). The equation of regression was y = 39020,92x + 196296, the limit of detection (LOD) value is 1,4920 μg / ml and the value of limit of quantitation (LOQ) is 4,9734 μg / ml. The precision test showed a coefficient of variation was 0.8711%. The result of determination of chloramphenicol content in ear drops were sample A = 1,17 %, sample B = 1,20 % and sample C = 1,19 %. Based on the test, samples of ear drops with contents crite-ria was fulfilled the requirements of Indonesian Pharmacopoeia fifth edition.